Making Sense of Epistemological Conflict in the Evaluation of Narrative Therapy and Evidence-Based Psychotherapy - Busch, Robbie; Strong, Tom; Lock, Andy (Massey University, 2011)
This paper outlines the epistemological and theoretical formation of narrative therapy and implications for its evaluation. Two authoritative paradigms of psychotherapy evaluation have emerged in psychology since the mid- 1990s. The Clinical Division of the American Psychological Association established the empirically supported treatment (EST) movement. A more inclusive but medically emulative model of evidence based practice in psychology (EBPP) then emerged. Some therapies such as narrative therapy do not share the theoretical commitments of these paradigms. Narrative therapy is an approach that values a non-expert based, collaborative, political and contextual stance to practice that is critical of normalising practices of medical objectification and reductionism. Post-positivist theoretical influences constitute narrative therapy as a practice that values the social production and multiplicity of meaning. This paper problematises a conflictual relationship (a differend) between the evaluation of narrative therapy and evidence based psychotherapy. Firstly, it briefly outlines the EST and EBPP paradigms and their epistemology. This paper then provides an overview of some of the key epistemological and theoretical underpinnings of narrative therapy and concludes with some cautionary notes on its evaluation.
This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License
Keywords: Evidence-based psychotherapy evaluation; Narrative therapy; Post-positivism; Empirically supported treatments; Evidence-based practice; Differend; Epistemology; Symbolic interactionism